Isoalantolactone Suppresses Tumor Progression by regulating Hippo-YAP Signaling in Cholangiocarcinoma cell - 임수빈 (The Graduate School, Ajou University, 2024)
Cholangiocarcinoma (CCA), which originates from bile duct epithelial cells, is a malignancy with poor prognosis owing to limited treatment. Here, we report the anti- cancer effect and mechanism of isoalanthoactone (IALT) through the Hippo pathway in CCA cells. In our study, we initially identified the cytotoxic effect of IALT, which inhibits cell proliferation and induces apoptosis in SNU478 cells, a CCA cell line. This effect stems from the regulation of MST1/2 and LATS1/2 by IALT, inducing phosphorylation of YAP, an oncogene of CCA, and inhibiting its activity. Therefore, the translocation to the nucleus of the YAP was inhibited, disrupting interaction with the TEAD transcription factor, thereby reducing the transcription of the YAP-target genes, CYR61 and CTGF. Furthermore, we found that IALT inhibits cell growth, cell migration, and CCA tumor formation in xenograft mouse model. Through LATS1/2-deficient cells, we confirmed the importance of LATS1/2 in the mechanism of IALT by showing a reduction in the effectiveness of IALT. Our data demonstrated that IALT functions as an anti-cancer drug by inhibiting YAP activity in CCA tumor progression. These findings propose a potential therapeutic agent for the treatment of CCA and highlight the importance of YAP-target therapies. Keywords: cholangiocarcinoma, isoalantolactone, Hippo pathway, YAP, LATS1/2, MST1/2, TEAD
학위논문(석사)--의생명과학과,2024. 2
Keywords: Cancer